The impact of global climate changes on the scarcity of water resources in Dhi Qar Governorate - Dr. Nasser Wali Farih; Dr.Mustafa Khairallah Lafta; Dr. Majeed Ali Shanawa (Journal of College of Education, 2025)
The research aims to uncover the causes of natural and human climate changes in Iraq in general, and in Dhi Qar Governorate in particular, and to analyze the magnitude and extent of these changes by understanding the amount of change during two recorded minor climatic periods at the Al-Nasiriya monitoring station, and to determine whether this amount is trending towards an increase, a decrease, or fluctuation. It also aims to assess the impact of these changes on the Iraqi environment in general and on the environment of Dhi Qar Governorate specifically, such as drought and desertification. The study of climate characteristics in Dhi Qar Governorate was conducted during two minor climatic periods from 1950-1961 and 2007-2018, considering the controlling factors. It was found that there is variation and quantifiable changes in the recorded climatic characteristics during these two periods at the Al-Nasiriya monitoring station for most climatic elements. It became evident that natural causes have a clear effect on climate changes, especially the fluctuation of solar radiation, while human factors also played a role in these changes due to the concentration of greenhouse gases as a result of the increasing population, which required burning more fossil fuels in various activities and fields. Moreover, the draining of marshes, deforestation, urban uses, explosions, and wars have contributed to the concentration of carbon dioxide and its subsequent impact on the Iraqi environment.Therefore, the concept of climate change is an implicit concept that falls under the concept of climatic alteration, as "change" refers to a gradual transition towards increase or decrease in climate elements and its phenomena, implying a transition in climate. Thus, the concept of climate change itself is a gradual transition from the current climate characteristics to other characteristics within the process of climatic alteration.
Keywords: global climate change ، scarcity of water resources ، Dhi Qar Governorate